Participação do macrófago e mediadores inflamatórios em modelo experimental de osteonecrose em camundongos swiss tratados com ácido zoledrônico - Abreu, Diego Feijão (2019)
Cancer is a public health problem, especially in developing countries. Bone metastases are considered as a frequent complication, associated with some malignancies. Bisphosphonates (BFs), drugs with antiresorptive activity, used in the treatment of bone metastases, osteoporosis and multiple myeloma cause bisphosphonate-induced osteonecrosis of the jaw (OMB), the main adverse effect. The pathogenesis of OMB is unknown, however, the process of inflammatory dysregulation and macrophages seem to be directly involved. The present work aims to delineate mediators related to the participation of macrophages in jaws of mice treated with zoledronic acid (AZ). Male swiss mice (n = 6 / group) were divided into 2 groups submitted to infusion with saline solution (0.1ml / kg) with or without exodontia and AZ (1mg / kg) with or without exodontia. Three weekly doses of AZ or saline (D0, D7, D14) were given intraperitoneally. After 28 days, the left and right lower first molars were extracted (D42), an additional dose of AZ or saline was administered the following week (D49) and one month after the exodontia (D70), ending the protocol. The animals were euthanized weekly and the jaws, after removal, were sectioned on the right side (LD) for n-acetyl-β-D-glucosaminidase (n-AG) and left side (LE) assays for microscopic evaluation (counting (NF-kB), TNF-α, cyclooxygenase-2 (COX-2), IL-1β, and MCP- 1. ANOVA / Bonferroni and t-student tests were used for statistical analysis (p <0.05). As a result, it was found that the percentage of empty osteocyte gaps was significantly higher in the group treated with day 14 (14.01 ± 1.73) day-old AZ than in day 70 (9.01 ± 3.97) (p <0.001). In the AZ group after exodontia, there was an increase compared to day 0 (1.33 ± 0.42) on day 42 (12.33 ± 0.76), and these values remained high until day 70 (11.33 ± 2.95 ) (p <0.001). The osteoclast count was significantly higher in the group treated with AZ submitted to the exodontia in relation to the other groups from day 49 to day 70 (p <0.001). The total number of inflammatory cells was significantly higher in the AZ group without exodontia on days 63 and 70 when compared to the saline group without exodontia in the same days (p <0.001). In the group AZ submitted to the exodontia the number of inflammatory cells was higher in relation to the other groups from day 49 to day 70 (p <0.001). Regarding the dosage of n-AG, the exodontia associated with the treatment with AZ increased the levels of n-acetyl glucosaminidase (p <0.001). Regarding the chemokine TNF-α, treatment with AZ increased its immunoexpression independent of exodontia (p <0.001). For IL-1β (p = 0.005) treatment with AZ increased its immunoexpression punctually. It is concluded that, the exodontia associated with AZ treatment increases the immunoexpression for COX-2 (p <0.001) and MCP-1 (p <0.001) at the surgical site and also increases the nuclear immunoexpression of NF-kB (p = 0.003). These results suggest, therefore, that immunological dysregulation involving macrophages may be associated with the pathogenesis of OMB.